Inorganic nanoparticles as potential regulators of immune response in dendritic cells. (July 2017) - Fogli, Silvia; Montis, Costanza; Paccosi, Sara; Silvano, Angela; Michelucci, Elena; Berti, Debora; Bosi, Alberto; Parenti, Astrid; Romagnoli, Paolo
Aim: The spontaneous adsorption of proteins on nanoparticles (NPs) in biological media is exploited to prepare complexes of NPs and proteins from cancer cells' lysates for application in cancer immunotherapy.Materials & methods: Gold (Au) and silica NPs were synthesized, incubated with cancer cells' lysates and characterized. Dendritic cells (DCs) were challenged with protein-coated NPs, their maturation, viability and morphology were evaluated and lymphocytes T proliferation was determined.Results: Silica and Au NPs bound different pools of biomolecules from lysates, and are therefore promising selective carriers for antigens. When incubated with immature DCs, NPs were efficiently endocytosed without cytotoxicity. Finally, protein-coated AuNPs promoted DC maturation and DC-mediated lymphocyte proliferation, at variance with lysate alone and protein-coated silica NPs, that did not promote DCs maturation.Conclusion: These results demonstrate that the spontaneous formation of protein coronas on NPs represents a possible approach to fast, easy, cost-effective DCs stimulation.